Feature Papers in Eng - Gil Bravo, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue is a collection of high-quality reviews and original papers from editorial board members, guest editors, and leading researchers discussing new knowledge or new cutting-edge developments in the field of engineering.